Joyce’s “Oxen of the Sun” Chapter: Parody or Pastiche? - Karrer, Wolfgang (FOCUS: Papers in English Literary and Cultural Studies, 2002)
The famous chapter 14 in James Joyce’s Ulysses has variously been called parody or pastiche (Houston 124). The words “parody,” “pastiche,” and “travesty” have a long history, and there have been many attempts to distinguish and relate the concepts behind them (Karrer 179-91, Hoesterey 1-15). In the last twenty years “travesty” has received less attention, although examples of its practice abound in contemporary media, and parody as well as pastiche have been linked to the postmodernist discussion by such critics as Linda Hutcheon, Fredric Jameson, and, more recently, Hillel Schwartz.